Twelve years of fin whale song evolution in the central North Pacific - Helble, Tyler A.; Guazzo, Regina A.; Dugan, Peter J.; Alongi, Gabriela C.; Martin, Cameron R.; Martin, Stephen W.; Henderson, E. Elizabeth (Frontiers in Marine Science, 2025)
Fin whale song consists of low frequency notes arranged in regular, repeating patterns of note type pairings and inter-note intervals (INIs). In the central North Pacific, fin whales use two downswept note types (A and B notes) with both singlet and doublet INIs that are interwoven throughout a song. These song patterns have been observed to change over time. Fin whale population size, structure, distribution, and connectedness are poorly understood, but monitoring their songs can help fill these knowledge gaps. In this study, we examine fin whale song patterns and their evolution across 12 years (2011–2023) with a focus on the most recent 5.5 years (2017–2023), expanding on our previous work. Between August 2017 and March 2023, automated detection, localization, tracking, and classification methods on 33 hydrophones at the Pacific Missile Range Facility (PMRF) off Kaua’i, Hawai’i enabled a detailed analysis of song patterns produced during 331 individual fin whale encounters that contained 130,402 notes. We categorized song patterns, quantified changes over time, and calculated cue rates in these fin whale tracks, detected between late fall and early spring. Five song patterns were observed, usually interwoven throughout a song with INIs of 30 s for A-A singlets, 17/32 s for A-A doublets, 34 s for B-B singlets, 16/23 s for B-B doublets, and 15/22 s for A-B doublets. A-B doublet has remained the dominant song pattern in this region and both A-B and B-A INIs have increased over time with the two INIs getting closer in recent years. While these five INI peaks persisted across seasons, certain INI distributions contained substantial variability and new patterns were observed. Our findings emphasize the need for nuanced acoustic analyses that account for note type and INIs. This analysis highlights the complexity of fin whale song and provides a robust foundation for long-term monitoring and comparative analyses across the North Pacific with song patterns serving as indicators of connectivity between different geographic regions. Ultimately this work can be applied to help define populations and the number of individuals in an area.